Terror, tortur og den tikkende bombe - Dige, Morten (Slagmark - Tidsskrift for idéhistorie, 2018)
The so-called “war on terror” has renewed the interest in torture in practice as well as in theory. The philosophical debate about possible justifications for torture has to a large extent revolved about the ticking time-bomb scenario: would it be justified to torture a terrorist in order to prevent a catastrophe? I criticize arguments based on ticking bomb scenarios in two steps. First, I show that exceptional resort to torture will not be possible in the situations where it is most needed. Second, I state several pragmatic as well as principled objections against a state sanctioned or tolerated practice of torture. Finally, I offer an explanation of what it means to regard the prohibition of torture as absolute.